Low Albumin Determination as a Biomarker Cancer with Cyclic Voltammetry in Agfilm/ITO and AgNOfilm/ITO Electrodes - Zulfa, Vinda Zakiyatuz; Farahdina, Ulya; Aziz, Ihwanul; Nasori, Nasori; Endarko, Endarko; Rhomadhoni, Muslikha Nourma; Rubiyanto, Agus (Trends in Sciences, 2023)
Ag and AgNO film were fabricated through sputter deposition on indium tin oxide (ITO) conductive glass. Electrochemical detection using cyclic voltammetry (CV) was carried out for low albumin levels in blood as a parameter of cancer patients. This study aims to determinate low albumin level as a biomarker cancer. Albumin adsorption on the Agfilm/ITO and AgNOfilm/ITO was also investigated to determine the level of sensitivity of both electrodes. Analysis of the CV measurements indicated that the Agfilm/ITO electrode was more sensitive compared to the AgNOfilm/ITO electrode, with a sensitivity value of 4.564 µA M-1cm-2 for the Agfilm/ITO electrode and 2.123 µA M-1cm-2 for the AgNOfilm/ITO electrode. The testing of albumin levels in blood within a range of low concentration levels between 10-1 and 10-8 g/dL indicated a detection limit of 10-9 g/mL. The selectivity of Ag electrodes was found to be very good for other interfering molecules such as urine, glucose, and lysozyme. The results of the modeling of electric field and magnetic field distribution showed that the Agfilm/ITO electrode possessed larger values than the AgNOfilm/ITO electrode. From this analysis, it can be concluded that the electrode modified with micro-sized Ag achieved more effective results than the electrode modified with AgNO. This sensor can determine low albumin level as a blood cancer biomarker. This sensor holds great promise for use in real samples in the future. HIGHLIGHTS Early detection with albumin biomarkers before metastasis cancer The testing of albumin levels with Cyclic Voltammetry and Electric Impedance Spectroscopy in the cancer within a wide range of low concentration levels (10-1 - 10-8) indicated a detection limit of 10-9 g/mL. The total mass of adsorbed BSA in electrode surface is more higher (281 mgm-2) than previous study. The Agfilm/ITO electrode exhibited high sensitivity and long-term stability for future applications. GRAPHICAL ABSTRACT